Insights of literacy on preventive behaviors of non-communicable diseases in Bangladesh: descriptive types of cross-sectional study among female university students - Banu, Bilkis; Chowdhury, Sujana Haque; Akter, Nasrin; Ara, Ulfat; Islam, Kazi Rakibul; Amin, M. Ruhul; Hossain, Sarder Mahmud (International Journal Of Community Medicine And Public Health, 2022)
Background: Non-communicable diseases were the leading global causes of mortality, causing more deaths compare to all other causes combined, which strike hardest at world’s low and middle-income countries. The aim of the study was to ascertain the health literacy and its practical application among the young generation to prevent major non communicable diseases. Methods: This was a descriptive type of cross-sectional study with 400 participants drawn from female university students of Dhaka, Bangladesh. Data were gathered by pre-tested, self-administered, structured and anonymous online questionnaires. Analysis was performed by using multivariate techniques followed by regression modelling and the margin of error was considered as 0.05. Results: Socio-demographic characteristics of the respondents showed that, majority of the female students belonged to age group <25 years. Study found that 63.5% of all university students had poor literacy on prevention of NCDs with female propensity. It was observed that highest level of poor literacy was about cancer (73.20%) and hypertension (75.20%) among all other NCDs. Statistically significant analysis observed that monthly lower family income <468 USD (AOR/p=1.73/0.01), respondents of businessman father (AOR=1.68/0.06) and residing in a family with >4 members (AOR/p=0.67/0.00) were the predictors for poor literacy about preventive health behavior on NCDs. Conclusions: This study revealed that the status of literacy on preventive health behaviors of NCDs among female university students was not satisfactory and very few had overall good literacy. This study found several important predictors under socio-demographic consequence played a significant role regarding poor literacy.